Religion som verdenshåndtering - Engberg-Pedersen, Troels (Dansk Teologisk Tidsskrift, 2014)
The article discusses two questions: whether (and in what sense) Christianity can be ‘naturalized’; and whether ancient Stoicism may contribute to a modern reformulation of ‘Christianity naturalized’. To answer these questions, the article focuses on articulating an understanding of ‘religion’ in relation to ‘science’. Building on the account given of the philosophical discipline of ‘ethics’ by Hilary Putnam in Ethics without Ontology, the article attempts to construct a structurally similar understanding of ‘religion’ (and its philosophical counterpart, ‘theology’) that will give it a legitimate position ‘in an age of science’ (cf. Putnam, Philosophy in an Age of Science). ‘Religion’ is here seen as one particular way of ‘coping with the world’. The article concludes by sketching some ways in which ancient Stoicism (as a specimen of a ‘natural philosophy and theology’) may help in reformulating an adequate, contemporary understanding of Christianity.